Reliability and Responsiveness of NutriQoL® Questionnaire. Issue 10 (October 2016) - Cuerda, Maria; Apezetxea, Antonio; Carrillo, Lourdes; Casanueva, Felipe; Cuesta, Federico; Irles, Jose; Virgili, Maria; Layola, Miquel; Lizán, Luis
Abstract Introduction NutriQoL® (Nestlé Health Science, Vevay, Switzerland) is a questionnaire developed to assess the health-related quality-of-life (HRQoL) of patients with home enteral nutrition (HEN) irrespective of their underlying condition and route of administration. The aim of this work is assessing the questionnaire's reliability and responsiveness to change. Methods Two cohorts of patients with HEN and their primary caregivers were enrolled to assess reliability and responsiveness, respectively. All participants had to be 18 years of age or older, without mental deterioration (≤3 or 4 errors in the Pfeiffer's test) and with sufficient functional status (>40 points on Karnovsky's performance status scale). When the patients' ability to respond to the questionnaire was impaired due to underlying disease, their caregivers answered on their behalf. NutriQoL was administered in two and three visits to reliability and responsiveness cohorts, respectively. Test–retest reliability and internal consistency were assessed by the intra-class correlation coefficient (ICC) and the Cronbach'sα, respectively. Responsiveness was evaluated by standardized effect size and standardized response mean between basal visit and third visit. Finally, the minimal clinically important difference (MCID) was estimated. Results A total of 54 and 86 participants were recruited to the reliability and responsiveness cohort, respectively. Thirty-five caregivers were selected to assess the inter-observer reliability. ICC values confirmed the good reproducibility level (ICC >0.75) of the questionnaire in both "physical functioning and activities of daily living" and "social life" domains and total score. The assessment of internal consistency in both domains of the questionnaire showed good internal consistency in visit 2. ICC showed the excellent agreement level between caregiver and patient in the global NutriQoL score. Finally, patients classified as having a minimal change in their health reported a mean (standard deviation) MCID in NutriQoL score of 0.63 (11.51). Conclusion NutriQoL is a reliable and unique instrument to measure the HRQoL in HEN patients. NutriQoL detects changes in the health status of the patient. Nevertheless, further research is needed to determine the full extent of the questionnaire responsiveness.